Evaluation of Grenache, Graciano and Tempranillo grape stilbene content after field applications of elicitors and nitrogen compounds. (12th October 2017) - Portu, Javier; López, Rosa; Ewald, Philipp; Santamaría, Pilar; Winterhalter, Peter; Garde‐Cerdán, Teresa
Abstract: BACKGROUND: Stilbenes have a significant biological activity and are one of the most important non‐flavonoid contributors to grape and wine health‐related properties. The accumulation of this class of compounds could be favored by viticultural practices such as the application of biostimulants. However, stilbene concentration also depends on several factors, including, for example, grape variety. Therefore, the aim of this work was to study the influence of foliar treatments carried out with elicitors (methyl jasmonate (MeJ) and a commercial foliar spray (YD)) and nitrogen compounds (phenylalanine and urea) on the grape stilbene composition of three varieties: Grenache, Graciano and Tempranillo. An ultra‐high‐pressure liquid chromatographic methodology was validated for stilbene determination. RESULTS: Results showed that, despite the huge influence of the grape variety, YD significantly improved stilbene composition in Grenache and Graciano, while MeJ increased the stilbene content in Graciano and Tempranillo. As for the nitrogen treatments, phenylalanine significantly increased the stilbene concentration in Graciano, while urea treatment increased it in Tempranillo. However, the application of elicitors had a greater effect than the nitrogen compounds. CONCLUSION: Overall, the foliar application of the elicitors could be a suitable practice for increasing the amount of stilbenes in grape and, therefore, its nutraceutical properties. © 2017 Society of Chemical Industry